Function and Regulation of Yeast Hexose Transporters - Özcan, Sabire (American Society for Microbiology, 1999)
Glucose, the most abundant monosaccharide in nature, is the principal carbon and energy source for nearly all cells. The first, and rate-limiting, step of glucose metabolism is its transport across the plasma membrane. In cells of many organisms glucose ensures its own efficient metabolism by serving as an environmental stimulus that regulates the quantity, types, and activity of glucose transporters, both at the transcriptional and posttranslational levels. This is most apparent in the baker’s yeast Saccharomyces cerevisiae, which has 20 genes encoding known or likely glucose transporters, each of which is known or likely to have a different affinity for glucose. The expression and function of most of these HXT genes is regulated by different levels of glucose. This review focuses on the mechanisms S. cerevisiae and a few other fungal species utilize for sensing the level of glucose and transmitting this information to the nucleus to alter HXT gene expression. One mechanism represses transcription of some HXT genes when glucose levels are high and works through the Mig1 transcriptional repressor, whose function is regulated by the Snf1-Snf4 protein kinase and Reg1-Glc7 protein phosphatase. Another pathway induces HXT expression in response to glucose and employs the Rgt1 transcriptional repressor, a ubiquitin ligase protein complex (SCF(Grr1)) that regulates Rgt1 function, and two glucose sensors in the membrane (Snf3 and Rgt2) that bind glucose and generate the intracellular signal to which Rgt1 responds. These two regulatory pathways collaborate with other, less well-understood, pathways to ensure that yeast cells express the glucose transporters best suited for the amount of glucose available.